How legal motivation buffers the effects of moral disengagement on school bullying among Chinese college students - He, Jianhua; Wang, Zhiqiang; Xu, Shuhui (Frontiers in Psychology, 2025)
BackgroundGrounded in Bandura’s social cognitive theory and the risk-buffering model, this study investigates how moral disengagement and legal motivation jointly influence school bullying among Chinese university students.MethodsA cross-sectional survey was administered to 409 students across mainland China. Confirmatory factor analysis established measurement validity. Pearson’s correlations and independent-samples t-tests assessed bivariate relationships, and moderation analysis using Hayes’ PROCESS macro tested whether legal motivation buffered the effect of moral disengagement on bullying.ResultsMoral disengagement correlated positively with bullying perpetration, while legal motivation correlated negatively. Moderation analysis revealed that higher levels of legal motivation attenuated the positive link between moral disengagement and school bullying.ConclusionEnhancing legal motivation may mitigate the influence of moral disengagement on bullying. Integrating legal-education initiatives with moral development interventions could therefore offer a more effective strategy for reducing school bullying.